2021
DOI: 10.3389/fneur.2021.747361
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels of Adolescents and Adults With Cerebral Palsy in Urban South Africa

Abstract: Background: Research in high income countries shows that people with cerebral palsy (CP) are less physically active than typically developing (TD) peers, but less is known regarding physical activity (PA) in those with CP in low-to-middle income countries. The aim of this study was to determine daily step count and levels of PA in adolescents and adults with CP living in urban South Africa, compared to TD peers, and to determine associations with sex, Gross Motor Function Classification System (GMFCS) level, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
0
2
Order By: Relevance
“…These differences were subtle ( Table 2 ), but it is worth noting that children with CP reported slightly more time in their PE and outside play compared to TD children. These findings were different to previous reports regarding physical activity level in young CP population in conjunction with TD children [ 16 , 17 , 18 ]. Comparing teenagers with CP (GMFCS level I–III) and their age-matched TD peers, a study from South Africa reported step counts were comparable [ 17 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These differences were subtle ( Table 2 ), but it is worth noting that children with CP reported slightly more time in their PE and outside play compared to TD children. These findings were different to previous reports regarding physical activity level in young CP population in conjunction with TD children [ 16 , 17 , 18 ]. Comparing teenagers with CP (GMFCS level I–III) and their age-matched TD peers, a study from South Africa reported step counts were comparable [ 17 ].…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were different to previous reports regarding physical activity level in young CP population in conjunction with TD children [ 16 , 17 , 18 ]. Comparing teenagers with CP (GMFCS level I–III) and their age-matched TD peers, a study from South Africa reported step counts were comparable [ 17 ]. However, a report from the Netherlands that compared physical activity level between children with CP (age 5–7 years, GMFCS level I-IV) and the same age TD peers showed lower physical activity level in children with CP than their counterpart TD children [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies measured functional outcomes using standardized and validated tools such as the GMFCS, the 66-item Gross Motor Function Measure, the Manual Ability Classification System (MACS), and the Communication Function Classification System (CFCS) to report the range of function among children living with CP (Table S 1). 9,11,19,20,32,38,41,43,46,54,63,94,[97][98][99][100][101][102] Studies of cohorts drawn from predominantly hospital-based neurology clinics tended to report a larger proportion of children with more severe gross motor impairments, that is, GMFCS or MACS levels IV and V, 11,20,38,41,46,63,83 compared to communitybased studies. 9,32,43,74,94,97,101 The difference in proportion was up to 55%, with a Ethiopian hospital-based study reporting 75.3% of children classified in GMFCS levels IV and V and 75.5% in MACS levels IV and V, 46 versus 20% of children in GMFCS levels IV and V in a community-based Ugandan study.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…9,11,19,20,32,38,41,43,46,54,63,94,[97][98][99][100][101][102] Studies of cohorts drawn from predominantly hospital-based neurology clinics tended to report a larger proportion of children with more severe gross motor impairments, that is, GMFCS or MACS levels IV and V, 11,20,38,41,46,63,83 compared to communitybased studies. 9,32,43,74,94,97,101 The difference in proportion was up to 55%, with a Ethiopian hospital-based study reporting 75.3% of children classified in GMFCS levels IV and V and 75.5% in MACS levels IV and V, 46 versus 20% of children in GMFCS levels IV and V in a community-based Ugandan study. 9 Many studies also reported varying functional impairments according to age, with a larger proportion of younger children more severely affected than older children.…”
Section: Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation